Effectiveness of different retention protocols in preventing posttreatment relapse after comprehensive orthodontic treatment - Afnan Alayyash (Wolters Kluwer Medknow Publications, 2024)
Background: After undergoing comprehensive orthodontic treatment, maintaining the achieved results and preventing relapse remains a significant concern. Various retention protocols have been proposed to address this issue, but their comparative effectiveness is not well-established. Materials and Methods: This study aimed to evaluate the effectiveness of different retention protocols in preventing posttreatment relapse following comprehensive orthodontic treatment. A sample of 150 orthodontic patients who had completed their treatment was included in the study. The patients were divided into three groups based on the retention protocol they received: Group A (Hawley retainers), Group B (Essix retainers), and Group C (permanent retainers). Patients' dental casts were obtained at the end of the treatment (T0) and six months after treatment (T1). Various measurements, including anterior and posterior occlusal changes, were recorded. Results: The results revealed that Group C (permanent retainers) showed the least amount of relapse compared to Groups A and B. In Group C, the mean anterior relapse was 0.2 mm, while in Groups A and B, it was 1.0 mm and 0.8 mm, respectively. Similarly, the mean posterior relapse in Group C was 0.1 mm, whereas in Groups A and B, it was 0.8 mm and 0.6 mm, respectively. These findings indicate that permanent retainers were more effective in preventing relapse compared to removable retainers. Conclusion: In preventing posttreatment relapse after comprehensive orthodontic treatment, permanent retainers demonstrated superior effectiveness compared to Hawley and Essix retainers.